The Impact Of DNK TV Community Press Agency on Increasing Public Speaking of FDIKOM Student - Lestari, Erlina Ayu; Wahyunengsih Wahyunengsih (Jurnal Ilmiah Teknik Informatika dan Komunikasi, 2023)
This research is entitled "The Impact of the DNK TV Community Press Institute on Increasing Public Speaking of Fdikom Students". The purpose of this research is to find out whether the DNK TV campus community has become the right place for students to improve public speaking skills, as well as whether Fdikom students, especially active members of DNK TV, can know and realize public speaking well. This study uses qualitative methods, namely observation and questionnaires. Questionnaires were distributed via Google form and filled out by Fdikom students who are active members of DNK TV. And observations are made by observing the activities carried out by active members directly in the field. The results of distributing questionnaires and field observations show that there are still some active members of DNK TV who have not implemented public speaking properly. However, this is balanced by the courage to try and self-confidence, so that the public speaking process continues to run well. DNK TV has also become the right place to develop skills and a place to find interesting, up-to-date and reliable information.